Comparison of anesthetic efficacy and adverse effects associated with peribulbar injection of ropivacaine performed with and without ultrasound guidance in dogs - Wagatsuma, Juliana T. [UNESP]; Deschk, Maurcio [UNESP]; Floriano, Beatriz P. [UNESP]; Ferreira, Joana Z. [UNESP]; Fioravanti, Heitor [UNESP]; Gasparello, Isabela F. [UNESP]; Oliva, Valeria N. L. S. [UNESP] (Amer Veterinary Medical Assoc, 2014)
Objective-To compare the anesthetic efficacy and adverse effects associated with peribulbar injection of ropivacaine (1% solution) performed with and without ultrasound guidance (UG) in dogs.Animals-15 dogs without ophthalmologic abnormalities.Procedures-Each dog was sedated and anesthetized. A peribulbar injection of ropivacaine (1% solution; 0.3 mL/kg) was performed with UG in 1 eye and without UG in the contralateral eye (control). For each eye, the intraocular pressure (IOP) immediately after eye centralization and number of punctures were recorded; ophthalmic complications, postinjection corneal sensitivity (determined by Cochet-Bonnet esthesiometry), durations of the sensory and motor blockades (the latter determined as the interval to restoration of the vestibuloocular reflex, pupillary light reflex, and conjugate eye movement), and blockade quality were assessed in both eyes following anesthetic recovery.Results-Needle placement was fully visualized in 8 of the 15 eyes injected with UG. For eyes injected with or without UG, there was no difference with regard to the number of punctures, postinjection corneal sensitivity, and sensory or motor blockade duration and quality; however, restoration of conjugate eye movement occurred later in control eyes. For eyes injected with UG, mean IOP was 18.6 mm Hg, compared with 23.3 mm Hg for control eyes. Incidence of subconjunctival hemorrhage was higher for control eyes; severity of chemosis and hyperemia varied over time within both groups of eyes.Conclusion and Clinical Relevance-In dogs, peribulbar injection of ropivacaine with UG is feasible in dogs and provides effective sensory and motor blockades similar to those achieved with conventional techniques.